1996
DOI: 10.1063/1.472677
|View full text |Cite
|
Sign up to set email alerts
|

Crossed-beam reaction of carbon atoms with hydrocarbon molecules. II. Chemical dynamics of n-C4H3 formation from reaction of C(3P j) with methylacetylene, CH3CCH (X1A1)

Abstract: The reaction between ground-state carbon atoms, C(3Pj), and methylacetylene, CH3CCH (X1A1), was studied at average collision energies of 20.4 and 33.2 kJ mol−1 using the crossed molecular beams technique. Product angular distributions and time-of-flight spectra of C4H3 at m/e=51 were recorded. Forward-convolution fitting of the data yields weakly polarized center-of-mass angular flux distributions isotropic at lower, but forward scattered with respect to the carbon beam at a higher collision energy. The transl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 53 publications
3
59
0
Order By: Relevance
“…The different product spectra could be the result of a combination of distinct production methods of the radicals (supersonic be-ams versus combustion flames) and different pressure conditions in the flame and within the supersonic expansion. Further, the present experiments support the prediction from previous crossed molecular beam studies of ground state carbon atom with methylacetylene at lower collision energies that a higher energy C 4 H 3 isomer, possibly of cyclic structure, likely contributes to reactive scattering signal [11]. Theoretically, the reaction mechanism was suggested based on electronic structure calculations of the triplet C 4 H 4 PES [25].…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The different product spectra could be the result of a combination of distinct production methods of the radicals (supersonic be-ams versus combustion flames) and different pressure conditions in the flame and within the supersonic expansion. Further, the present experiments support the prediction from previous crossed molecular beam studies of ground state carbon atom with methylacetylene at lower collision energies that a higher energy C 4 H 3 isomer, possibly of cyclic structure, likely contributes to reactive scattering signal [11]. Theoretically, the reaction mechanism was suggested based on electronic structure calculations of the triplet C 4 H 4 PES [25].…”
Section: Discussionsupporting
confidence: 76%
“…The n-C 4 H 3 isomer (HCCCHCH; X 2 A') was identified as a reactive intermediate formed in the initial addition of the ethynyl radical (CCH) to acetylene (HCCH). However, a detailed analysis of the center-of-mass functions as extracted from the crossed beam reactions of ground state carbon atoms with methylacetylene [11] suggested that an elusive high-energy isomer, might have also been synthesized. The molecular structure of this isomer is still unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in contrast to the reactions of ground state carbon atoms, C( 3 P j ), with allene and methylacetylene, where under single collision conditions only the C s symmetric, resonantly stabilized i-C 4 H 3 radical was formed. 38,41 Because in the allene system, the hydrogen atoms are equivalent, it is not feasible to utilize partially deuteration of the reactants as done in the methylacetylene-d 3 reaction to elucidate the role of thermodynamically less stable isomers p2-p4 on the reaction dynamics. A comprehensive study of the global BC 3 H 4 PES combined with RRKM calculations is currently underway.…”
Section: Discussionmentioning
confidence: 99%
“…Kaiser et ale (1996b); b. Kaiser et al (1996a); c. Kaiser et al (1996c); d. Kaiser et al (1997a); e. Kaiser et ale (1999a)j f. Kaiser et aI. (1997b); g. Kaiser et al (1999b) The explicit identification of the carbon-hydrogen exchange under single collision conditions opens a versatile, one step pathway to free hydrocarbon radicals in extraterrestrial environments and even in our solar system.…”
Section: Reactants Productsmentioning
confidence: 99%